The Cell: A Very Short Introduction - Allen, Terence and Cowling, Graham (New York Oxford University Press, 2011)
All living things on Earth are composed of cells. A cell is the simplest unit of a self-contained living organism, and the vast majority of life on Earth consists of single-celled microbes, mostly bacteria. These consist of a simple 'prokaryotic' cell, with no nucleus. The bodies of more complex plants and animals consist of billions of 'eukaryotic' cells, of varying kinds, adapted to fill different roles - red blood cells, muscle cells, branched neurons. Each cell is anastonishingly complex chemical factory, the activities of which we have only begun to unravel in the past fifty years or so
Includes Index and Illustrations.
Keywords: Cells -- Popular works